The transferability and performance of payment-by-results biodiversity conservation procurement auctions: empirical evidence from northernmost Germany - Markus Groth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
Managed grasslands contribute in a number of ways to the biodiversity of European agricultural landscapes and provide a wide range of ecosystem services that are also of socio-economic value. Against the background of a rapid biodiversity loss in agricultural landscapes, increasing attention is being paid to farming practices that enhance ecosystem services. Therefore developing cost-effective conservation payment schemes is the main challenge facing present European agri-environmental policy. This paper deals with the transferability of a payment scheme that combines a payment-by-results approach with the use of discriminatory-price conservation procurement auctions in order to improve the cost-effectiveness of conservation schemes for grassland plant biodiversity. Hence the design, implementation and results of the adapted case-study payment scheme in the county Steinburg in the northernmost federal state of Germany (Schleswig-Holstein) will be focussed. Results concerning the ecological-effectiveness of the payment-by-results approach as well bid-prices and potential cost-effectiveness gains by the use of conservation procurement auctions point out that it was possible to transfer the payment scheme successfully to another region, whereby the adapted case-study even.
Keywords: C93; D44; H41; Q24; Q28; Q57; R52; 330; Agri-environmental policy; discriminatory-price auction; ecological services; experimental economics; multi-unit auction; payment-by-results; plant biodiversity; rural development; outperforms the original case-study